Investigating the Relationship between Emotional Intelligence and Academic Achievement in Anesthesiology and Operating Room Students of Tehran University of Medical Sciences - Aeen Mohammadi; Rita Mojtahedzadeh; Afzal Shamsi (Tehran University of Medical Sciences, 2019)
Background and Aim: Studentschr('39') academic achievement is one of the important indicators in evaluating the educational system. Emotional intelligence is one of the success factors in educational environments that can predict success in different aspects of life.The purpose of this study was to determine the relationship between emotional intelligence and academic achievement in students of Anesthesiology and Operating Room of Tehran University of Medical Sciences. Materials and Methods: This cross-sectional study was performed on 140 people of anesthesiology students and operating room of Tehran University of Medical Sciences in 2018. The samples were selected by available method. The instrument consisted of two demographic questionnaires and the Bradbury and Graveschr('39') standard questionnaire for emotional intelligence. In order to measure academic achievement, the average score of the whole course of the students was used. Data were analyzed by SPSS software and P<0.05 was considered as significant. Results: Pearsonchr('39')s correlation coefficient showed a significant positive correlation between academic achievement and total emotional intelligence(r=0.554) and all its dimensions(self-awareness, self-management, social awareness and relationship management)(P=0.000). The mean score of emotional intelligence in female students(114.11±11.40) was higher than that of male students(113.39±12.57)(P=0.887). Conclusion: The mean score of studentschr('39') emotional intelligence and its dimensions was in a desired level. There was a positive and significant relationship between emotional intelligence and all aspects of it with academic achievement. Therefore, it is essential for the authorities to plan for the improvement of the level of emotional intelligence for the studentschr('39') academic achievement.